A class of sulfonamide carbonic anhydrase inhibitors with neuropathic pain modulating effects. Issue 8 (15th April 2015) - Carta, Fabrizio; Di Cesare Mannelli, Lorenzo; Pinard, Melissa; Ghelardini, Carla; Scozzafava, Andrea; McKenna, Robert; Supuran, Claudiu T.
Graphical abstract: Abstract: A series of benzene sulfonamide carbonic anhydrase (CA, EC 4.2.1.1) inhibitors which incorporate lipophilic 4-alkoxy- and 4-aryloxy moieties, together with several derivatives of ethoxzolamide and sulfanilamide are reported. These derivatives were investigated as inhibitors of the metalloenzyme carbonic anhydrase (CA, EC 4.2.1.1) of which multiple isoforms are known, and some appear to be involved in pain. These sulfonamides showed modest inhibition against the cytosolic isoform CA I, but were generally effective, low nanomolar CA II, VII, IX and XII inhibitors. X-ray crystallographic data for the adduct of several such sulfonamides with CA II allowed us to rationalize the good inhibition data. In a mice model of neuropathic pain induced by oxaliplatin, one of the strong CA II/VII inhibitors reported here induced a long lasting pain relieving effect, a fact never observed earlier. This is the first report of rationally designed sulfonamide CA inhibitors with pain effective modulating effects.